Catalytic Behavior and In Situ X‐Ray Diffraction of Promoted Iron Catalysts for Fischer‐Tropsch Synthesis. Issue 11 (1st October 2022) - Wen, Ruoxi; Thiessen, Johannes; Jess, Andreas
Abstract: The effects of structural promoters (ZnO, SiO2, and Al2 O3 ) on the phase transformation during reduction and Fischer‐Tropsch synthesis (FTS) of a FeCuK catalyst were investigated by in situ X‐ray diffraction and the FTS catalytic performance was studied in a fixed‐bed reactor. The reduction follows the path of Fe2 O3 /K2 Fe22 O34 → Fe3 O4 → α ‐Fe. The addition of ZnO, SiO2, and Al2 O3 delayed and prolonged the reduction. The iron carbides formed under reaction conditions were χ ‐Fe5 C2 and ε ‐Fe2 C. The presence of ZnO, SiO2, and Al2 O3 favored the formation of χ ‐Fe5 C2 . ε ‐Fe2 C is a more active phase. Besides, ε ‐Fe2 C seems to favor the formation of CO2 and C5+ and χ ‐Fe5 C2 benefits CH4 and C2 –C4 products. Abstract : Addition of structural promoters to the iron‐based catalysts for Fischer‐Tropsch synthesis can increase dispersion and physical attrition of the catalysts and also have an influence on the iron carbide phases. This research combined in situ XRD and a fix‐bed reactor to study if a correlation between the iron carbides and FTS catalytic performance exists.